Cover Feature: Naked Eye, Ratiometric Absorption, and Ratiometric Fluorescence for Lead‐Ion Analysis with a Triplex‐Signal Chemosensor (Eur. J. Inorg. Chem. 18/2018). Issue 18 (14th April 2018) - Ma, Pan; Wang, Yucheng; Qi, Qun; Dong, Xiaoru; Zhu, Peihua; Yu, Jinghua
Abstract : The Cover Feature shows a PDI–porphyrin based triplex‐signal chemosensor for detection of Pb 2+ . More interestingly, the binding of these two PDI–porphyrin compounds with Pb 2+ induces not only a color change visible directly with the naked eye, but also remarkable changes in the signal ratio of two absorption/emission bands. This can be used for a preliminary test of Pb 2+ as well as the precise detection of Pb 2+ by ratiometric fluorescence. This research provides a practical strategy for the rational design of novel functional probes for many useful applications in real systems. More information can be found in theFull Paper by P. Zhu et al.